PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI DAN ORIENTASI PASAR TERHADAP KINERJA PELAKU UMKM GERAI PONSEL DI KECAMATAN MEDAN AMPLAS - Dina Damayanti; Adrial Falahi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of the use of information technology and market orientation on the performance of MSME actors at cellphone outlets in Medan Amplas District. This study uses descriptive and quantitative methods, the population is all the owners of mobile phone outlets in the District of Medan Amplas as many as 84 cell phone outlets. The location of this research is the Mobile Phone Outlet in Medan Amplas Subdistrict, North Sumatra, which starts from January to October 2022. The sampling technique for this research uses Saturated Samples, so that the research sample is set at 84 cellphone outlets. The results of this study indicate the multiple linear regression equation obtained by the equation Y = 1.369 + 0.355X1 + 0.532X2. The results of the t-test obtained that the value of tcount = 7.705 > ttable 1.663 and a significance of 0.000 <0.05, then Ha is accepted and Ho is rejected, which means that the Information Technology variable (X1) partially has a significant influence on the performance of MSME actors in Mobile Phone Outlets in Medan Amplas District. The value of tcount = 4.377 > ttable of 1.663 and a significance of 0.003 <0.05, then Ha is accepted and Ho is rejected, which means that the Market Orientation variable (X2) partially has a significant influence on the performance of MSME actors in Mobile Phone Outlets in Medan Amplas District. The results of the F test obtained a positive value of Fcount = 79,171>Ftable = 2.72 and a significance of 0.000 <0.05, meaning that information technology and market orientation variables simultaneously have a positive and significant effect on the performance of MSMEs at Mobile Phone Outlets in Medan Amplas District. The value of Adjusted R Square (R2) is 0.842 or 84.2%, while the remaining 15.8% is explained by other variables not examined in this study. So this research concludes that the use of Information Technology (X1) and Market Orientation (X2) affects the performance of MSME Actors at Mobile Phone Outlets (Y) in Medan Amplas District.